SUSTAINABLE DEVELOPMENT REVIEW - Kunarto Kunarto; Budi Prasetyo (UNTAG Law Review, 2022)
An overview of sustainable development in Indonesia is a concept of sustainable development that is of concern to development actors, including the government. The problem of development in meeting the needs of many emerging impacts on the declining quality of the environment. Therefore, a sustainable development concept is needed. There are many problems related to sustainable development, but we can formulate these problems: what is the definition and concept of sustainable development in Indonesia?Sustainable development is development that aims to meet the needs of current and future generations. To fulfill this concept, an implementation strategy is needed, there are 4 (four) things that need to be considered, namely: equity, participation, diversity, integration and long-term perspective.